Ambient electrochemical NH3 synthesis from N2 and water enabled by ZrO2 nanoparticles. Issue 25 (2nd March 2020) - Xu, Tong; Ma, Dongwei; Li, Chengbo; Liu, Qian; Lu, Siyu; Asiri, Abdullah M.; Yang, Chun; Sun, Xuping
Abstract : ZrO2 nanoparticles act as an efficient electrocatalyst for ambient N2 -to-NH3 fixation. In 0.1 M HCl, it attains a large NH3 yield rate of 24.74 μg h −1 mgcat. −1 with a faradaic efficiency of 5.0% at −0.45 V vs. RHE. Abstract : Industrially, artifical N2 fixation to NH3 mainly relies on the Haber–Bosch process which is operated in a harsh environment with large energy consumption and heavy serious greenhouse gas emission. Electrochemical N2 reduction offers a carbon-neutral and energy-saving method for NH3 synthesis under ambient conditions. Herein, we demonstrate the first use of ZrO2 nanoparticles as an earth-abundant electrocatalyst for NH3 synthesis from N2 and water under ambient conditions. In 0.1 M HCl, the electrocatalyst presents a large NH3 yield rate of 24.74 μg h −1 mgcat. −1 with a faradaic efficiency of 5.0% at −0.45 V vs. the reversible hydrogen electrode. It also demonstrates high electrochemical stability and excellent selectivity for NH3 generation.